THE IMPORTANCE OF INTEGRATING MULTICULTURALISM IN TEACHING COMMUNITY INTERPRETING - Fitrotul Maulidiyah (Universitas Islam Malang, 2021)
Globalization and massive development in communication and information technology generates multiculturalism in the last few years. It enables people live their originality consciously and without authorization of the other cultures. In other words, multiculturalism is a cultural wealth for living together. Furthermore, people who have different cultures consider that it is necessary to find a way to have proper intercultural communication especially when they live together. Multiculturalism is considered compulsory for social diversity including its appearance and recognition. Moving from this thought, interpretation, a social phenomenon between different languages and cultures has an undeniable function especially for community interpretating. The function of community interpreting and intercultural communication is multifaceted. The community interpreter has to know the languages, the cultures they belong to, their social structures, world understandings and value judgments. Multiculturalism needs social and cultural diversity. Therefore, a community interpreter has to apply every culture’s necessities equally besides the interpreting procedures. In multicultural societies formed by different cultures, community interpreting plays a pivotal role in order to live together peacefully towards common boundaries. Community interpreting has a mission on conciliation and adaptation of different cultures and values. Community interpreting helps social structures compromise in the sense of multiculturalism and recognize their cultural background. This study will examine the necessity of multiculturalism integration in the teaching of community interpreting which has become more important in recent days. This is intended for communities with diverse cultures to continue their harmonious coexistence and to maintain their presence in the content of multiculturalism.Keywords: community interpreting, integration, multiculturalism